Rise and Fall of the Constitutional Right to a Jury Trial for Criminal Cases in the United States - Arrieta Caro, José (2017)
Since its appearance in Europe, the trial by jury had to travel a long path until it became the official procedure to try criminal cases in the United States. Although it was not really created with that specific purpose, over the years it experienced memorable moments in which it was granted with the prestige and value required to be inserted in the Constitution of that country, as a safeguard against the arbitrariness of the governmental power. Today, however, the great importance that it had in the past has significantly decreased. The needs and practices of a system with a particularly high rate of convictions have relegated and transformed it into a real endangered specie. The following article describes and explains its birth and rise, as well as its subsequent virtual disappearance due to the not so efficient as dangerous guilty pleas.